The Morphological Variations of Culex pipiens Larvae (Diptera: Culicidae) in Yazd Province, Central Iran - H Dehghan; J Sadraei; SH Moosa-Kazemi (Tehran University of Medical Sciences, 2010)
Background: Culex pipiens complex shows variations in morphological and biological characters including different biological forms and has medical and veterinary importance. Because of having morphological variations, sometimes it is not easy to separate this species from Cx. quinquefasciatusand Cx. torrentium.The aim of this study was to  identify the  Culex pipiens complex species in order to use in control programs in the future. Methods: This study was carried out in two randomly selected rural villages in Yazd County, eastern Iran using dipping technique from April to October 2009. The data were analyzed using SPSS software version 16. Results: Average of siphon index in fourth-instrar larvae was 3.86±0.03, the minimum and maximum were calculated 2.43 and 5.14, respectively. Siphon/Saddle index was measured as average, minimum and maximum 3.2±0.2, 2.78, and 4.42 respectively. In our study, only 4 specimens had single seta 1 on segments III and VI (2.5%) and the remaining beard double seta (97.5%). The maximum 3-6 branches seta 1a-S and 1b-S (95%) were observed on siphon. Conclusion: More populations of Culex pipiens from different areas of Iran need to be studied to gain complete information about the taxonomy and ecology of the species in the country.